Answer:
y = -6/5x + 3
Step-by-step explanation:
y = mx + c (or b, depending on where you're from)
Slope = m = -6/5
y = -6/5x + c
You can sub (0, 3) and (5, -3) into y = -6/5x + c and they both have the same answer where c = 3
Therefore, the equation is y = -6/5x + 3
Hop this helps
Answer:
no solution
Step-by-step explanation:
we have point (-6, - 1)
Now we will put these points in each equation,
y = 4x +23
put x = -6 and y = -1
-1 = 4 (-6) +23
-1 = -24 + 23
-1 = -1
LHS = RHS, so this equation has (-6 , -1) as solution.
y = 6x
put x = -6 and y = -1
-1 = 6 (-6)
-1 not= -36
LHS is not equal RHS, so (-6 , -1) is not a solution for that equation,
y = 3x - 5
put x = -6 and y = -1
-1 = 3 (-6) - 5
-1 = -18 - 5
-1 not= -23
LHS is not equal RHS, so (-6 , -1) is not a solution for that equation,
y= 1/6 x
put x = -6 and y = -1
-1 = -6/6
-1 = -1
LHS = RHS, so (-6 , -1) is a solution for that equation,
There would be a hole when x = -4.
If you factor both the top and the bottom, you will see that the factor (x + 4) is in both the numerator and denominator. Therefore, the would be a hole when x = -4 because that would also make the denominator 0.
Answer:
glizzy
Step-by-step explanation: